KARAKTER MASYARAKAT DESA DAN KOTA: TINJAUAN KRITIS IBNU KHALDUN TERHADAP MASYARAKAT MILLENIAL - Syukron Ma'mun; Taufiq Zaenal Mustofa (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2022)
This article reveals two comparisons of the character of the rural (badawa) and urban society (hadhara), attributed to modernism and globalism that enter all the lines of Indonesian society today, so that they loss of their identity. Luxurious life is a warm conversation and a must and everyone's dream. This article is a critical study of library research with a qualitative approach. The data used in this research are concept data of rural and urban society in the view of Ibn Khaldun and other data supporting it. The source of data used in this study includes three sources, namely: Primary, Ibn Khaldun's Al-Muqaddimah, secondary sources include: Epistemology of the Critical History of Ibnu Khaldun by Toto Suharto, Ibn Khaldun and the Islamic Thought Pattern by Fuad Baali and Ali Wardi, Community Development of Islam Paradigm (Epistimological Studies of the Thought of Ibn Khaldun) by Wendi Melfa and Solihin Siddiq, Historical philosophy of Ibn Khaldun Zainab al-Khudhairi and other books. As well as tertiary sources or complementary sources such as Introduction to Sociology, Classical and Modern Sociological Theory, by George Ritzer, Rodney Stark's Sociology Second Edition, and others. The results of the analysis explain that every society has its own characteristics; the character comes from the influence of the environment and geographical location. Among the villagers' character is life simple, not greedy, help each other, open, more firm and original. While the character of the city people live in lavish, consumptive, closed and greedy, weaker soul, and urban. That there has been a shift in meaning and values in the life of society. For example, the first values of togetherness (mutual assistance), courtesy, friendliness, and religious trends are still highly respected, but because of the current globalization, these values are far away and almost lost. We can feel before the flow of information technology globalization, communication is still based on a sense of kinship, but after globalization it echoes the communication is changing based on needs.